Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Publisher: 6876
Keywords: Bibliographie; Nettoyer

Winnipeg comedy club bans discrimination, hatefulness, harassment | CBC News - Gibson, Shane (CBC, 2018)
Wee Johnny’s comedy room posted a sign this week warning that anyone violating a new anti-harassment policy — which bans “sexism, racism, homophobia, transphobia, physical intimidation or any other form of abusive behaviour” — may be asked to leave the club.

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Publisher: Intellect
Keywords: Irina

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Number: 1
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

'Shocking' level of sexual harassment at music festivals (BBC News, 2018)
Up to 43% of women under 40, who have been to a music festival, say they have faced unwanted sexual behaviour.

The music business’s gender pay gap is embarrassing and uncomfortable. It’s time for change. (Music Business Worldwide, 2018)
MBW Contributing Editor, Rhian Jones, gives her take on the news…

“Essential—Passion for Music”: Affirming, Critiquing, and Practising Passionate Work in Creative Industries - Bennett, Toby (The Palgrave Handbook of Creativity at Work, 2018)
This chapter considers “passion” as an enthusiastic orientation to work within creative worlds: work motivated by intense attachments to the products of work and their conditions of production. Drawing on Luc Boltanski’s pragmatic sociology of critique and justification, the chapter argues that the passionate lens most usefully trains our sights on normative questions: not what or how—but why such work is undertaken. Embedded in research on cultural and creative industries, the contemporary recorded music sector is presented as a “passionate” industry in transformation. Interviews with workers, who both criticize and defend their industry, act as a springboard to explore three possible interpretive approaches: affirmative, critical, and pragmatic. Theoretical flexibility is needed to keep “passion” open to future inquiry—particularly regarding inequalities in creative work.

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)